Understanding vaccine hesitancy: Insights from social media on polio, human papilloma virus, and COVID-19 in Zambia - Samuel Munalula Munjita (Digital Health)
Objectives Vaccine hesitancy remains a critical challenge to public health in Zambia and globally, necessitating a deeper understanding of the factors influencing this phenomenon. The study analyzed user-generated Facebook comments from January 2021 to December 2023 to understand the factors influencing vaccine hesitancy in Zambia. Methods This study employed a qualitative case study design, focusing on the official Facebook page of the Ministry of Health in Zambia. A purposeful sampling technique was used, collecting comments that discussed vaccine hesitancy related to polio, human papilloma virus (HPV), and coronavirus disease 2019 (COVID-19) vaccines. Results The analysis revealed that men contributed 77.5% of comments followed by women with 22.5%. The majority of comments (82.5%) pertained to COVID-19 vaccines, followed by polio (14.1%) and HPV (3.4%). Notably, women expressed greater hesitancy toward polio vaccines (60%) compared to COVID-19 (19.9%) and HPV (12.5%). Thematic analysis highlighted significant hesitancy against vaccines shaped by vaccine safety and efficacy concerns, frequent calls for vaccination particularly against polio, conspiracy theories, distrust in health authorities, and poor communication from health authorities. Other drivers of vaccine hesitancy were reliance on spiritual beliefs, herbal remedies and natural immunity, and the pervasive spread of misinformation. Conclusion These findings underscore the barriers to vaccine acceptance, emphasizing the critical need for transparent communication and community engagement. To improve vaccine uptake, public health strategies must address community-specific concerns, foster trust, and enhance the effectiveness of health communication efforts.